Renewable energy development towards indonesia’s energy transition: Technological innovations for a sustainable future - Fahmi, Yunita (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2025)
Background: Global climate change has significantly impacted Indonesia, leading to various challenges such as water scarcity, the degradation of marine and land ecosystems, and food instability. These environmental issues are also affecting public health and the nation's economy. Increased frequency of natural disasters like floods, landslides, and droughts is resulting in agricultural losses, while rising sea temperatures and changing seawater composition threaten fishery resources. Addressing these issues is critical for both environmental preservation and strengthening Indonesia's economy. Method: This study employs a literature review approach to explore Indonesia's strategy for transitioning to renewable energy. By analyzing various sources and reports, the paper aims to understand the country's energy transition and the economic and environmental implications of continuing reliance on non-renewable energy. Findings: The study finds that Indonesia is facing significant negative impacts from climate change, which are expected to cause economic losses ranging from 0.66% to 3.45% of GDP by 2030. These impacts are particularly due to the use of non-renewable energy sources. Transitioning to renewable energy is viewed as a vital solution for mitigating these losses, but it requires collaboration from government bodies, communities, and the private sector. Conclusion: Efforts to mitigate climate change and adapt to its impacts are crucial for the sustainability of Indonesia's economy, public health, and environmental preservation. A transition to renewable energy is essential, but it requires concerted efforts from various stakeholders to ensure its success and address the broader challenges posed by climate change. Novelty/Originality of this Study: This study offers a comprehensive review of Indonesia’s renewable energy transition strategy, providing new insights into how mitigating the impacts of climate change through renewable energy could contribute to economic sustainability. The analysis emphasizes the collaborative approach needed from multiple stakeholders to address the challenges of climate change and transition away from non-renewable energy sources.